Construction of macromodels of nonlinear dynamical systems using optimization - Stakhiv, Petro; Kozak, Yuriy; Hoholyuk, Oksana (Publishing House of Lviv Polytechnic National University, 2011)
The usage of macromodels in the process of design and analysis of modern dynamical systems allows significant reducing of required computation efforts because it makes it possible to ignore not important effects for particular analysis. This causes the necessity of developing universal approaches intended for the construction of macromodels of the complex dynamical object in the form that is useful for their further analysis. The analysis of problems faced while constructing macromodels of nonlinear dynamical systems with the use of optimization has been provided in this paper, as well as the recommendations for their possible solutions. Використання макромоделей в процесі проектування сучасних динамічних систем дозволяє значно знизити обчислювальні затрати, оскільки дозволяє не враховувати несуттєві явища для конкретного аналізу. Це приводить до необхідності розробки універсальних і ефективних підходів до побудови макромоделей складних нелінійних динамічних об’єктів у зручній для подальшого використання формі. В даній статті проводиться аналіз проблем, які виникають на шляху побудови макромоделей нелінійних динамічних систем з використанням оптимізації і даються рекомендації щодо їх можливого вирішення.
Побудова макромоделей нелінійних динамічних систем з використанням оптимізації
Keywords: macromodel construction; macromodels; optimization; model paramenters identification